DAMPAK CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN SEKTOR MANUFAKTUR LISTING DI BEI - Jurnal Akuntansi Barelang (LPPM Universitas Putera Batam, 2017)
The purpose of this research is to examine the impact of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) is measured by proxy of Audit Committee on Corporate Value (PBV). This study uses secondary data from the Annual Report and Financial Report of public companies listed on the Indonesia Stock Exchange. The object of research is on the manufacturing companies listing on the Indonesia Stock Exchange in the period 2010-2014. Data analysis technique used is multiple linear regression analysis. The results show that CSR and GCG (Audit Committee) simultaneously have a significant positive effect on Corporate Value on manufacturing companies listing on Indonesia Stock Exchange in period 2010-2014. Partially only CSR has a significant positive effect on Corporate Value. While the GCG (Audit Committee) partially does not affect the value of the Company in manufacturing companies listing on the Indonesia Stock Exchange in the period 2010-2014.